Revitalisasi Pertanian Berkelanjutan Melalui Jagung Komposit Dan Pengolahan Sampah Organik di Nagari Simpang Pasaman - Fitri Ekawati; Irfan Suliansyah; Yulistriani; Siti Nurhasanah; Yana Antika Sari; Risky Syahputra; Zhafira Syarafina (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: Nagari Simpang, Pasaman Regency, is an agrarian area where maize is the main commodity, cultivated using conventional practices that rely heavily on hybrid seeds and inorganic fertilizers. In the long term, this pattern leads to increased production costs, declining soil fertility, and low added value of agricultural products. In addition, suboptimal household waste management contributes to environmental pollution. This community service program aimed to revitalize a sustainable maize farming system through the integration of composite maize seeds and organic waste processing technology. The program was conducted from July to November 2025, involving approximately 30 farmers. The methods included an initial survey, program socialization, training on organic fertilizer production, establishment of a composite maize demonstration plot, and evaluation using pre-test and post-test. Data were analyzed using descriptive quantitative methods. The results showed an increase in participants’ understanding of composite maize seeds and improved skills in producing organic fertilizer. Higher post-test scores (3-4,2) compared to pre-test (1-2) indicate the effectiveness of the training and mentoring approaches. Additionally, there was an increase in community awareness regarding the utilization of organic waste. This program contributed to enhancing farmers’ capacity and independence and serves as an initial step toward developing a sustainable agriculture system based on local resources. Keywords: composite maize; household waste; community empowerment; sustainable agriculture; organic fertilizer Abstrak: Nagari Simpang, Kabupaten Pasaman merupakan wilayah agraris dengan komoditas utama jagung yang dikelola secara konvensional dan bergantung pada benih hibrida serta pupuk anorganik. Pola ini dalam jangka panjang menyebabkan peningkatan biaya produksi, penurunan kesuburan tanah, serta rendahnya nilai tambah hasil pertanian. Selain itu, pengelolaan limbah rumah tangga yang belum optimal berdampak pada pencemaran lingkungan. Kegiatan pengabdian ini bertujuan merevitalisasi sistem pertanian jagung berkelanjutan melalui integrasi benih jagung komposit dan teknologi pengolahan sampah organik. Kegiatan dilaksanakan selama Juli–November 2025 dengan melibatkan ±30 petani. Metode meliputi survei awal, sosialisasi, pelatihan pembuatan pupuk organik, pembuatan demplot jagung komposit, serta evaluasi menggunakan pre-test dan post-test. Data dianalisis secara deskriptif kuantitatif. Hasil menunjukkan adanya peningkatan pemahaman mitra terkait benih jagung komposit serta peningkatan keterampilan dalam memproduksi pupuk organik. Skor post-test yang lebih tinggi (3-4,2) dibandingkan pre-test (1-2) menunjukkan efektivitas metode pelatihan dan pendampingan. Selain itu, terjadi peningkatan kesadaran lingkungan masyarakat terhadap pemanfaatan sampah organik. Kegiatan ini berkontribusi dalam meningkatkan kapasitas dan kemandirian petani serta menjadi langkah awal pengembangan sistem pertanian berkelanjutan berbasis sumber daya lokal. Kata kunci: jagung komposit; limbah rumah tangga; pemberdayaan masyarakat; pertanian berkelanjutan; pupuk organik